2022
DOI: 10.1089/tmj.2021.0101
|View full text |Cite
|
Sign up to set email alerts
|

Remote Patient Monitoring Identifies the Need for Triage in Patients with Acute COVID-19 Infection

Abstract: Background: Telehealth was frequently used in the provision of care and remote patient monitoring (RPM) during the COVID-19 pandemic. The Precision Recovery Program (PRP) remotely monitored and supported patients with COVID-19 in their home environment. Methods: This was a single-center retrospective cohort study reviewing data acquired from the PRP clinical initiative. Results: Of the 679 patients enrolled in the PRP, 156 patients were screened by a clinician following a deterioration in symptoms and vital si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Few studies have assessed the effect of monitoring patients with pulse oximeters on health outcomes and the use of health-care services. 37 , 67 A prospective trial estimated an almost 50% reduction in unnecessary emergency and hospital readmissions among participants. 44 In a study by Shah and colleagues, 54 33% of participants stated that they would be more likely to visit hospitals, at least for reassurance, if they were not monitored remotely.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have assessed the effect of monitoring patients with pulse oximeters on health outcomes and the use of health-care services. 37 , 67 A prospective trial estimated an almost 50% reduction in unnecessary emergency and hospital readmissions among participants. 44 In a study by Shah and colleagues, 54 33% of participants stated that they would be more likely to visit hospitals, at least for reassurance, if they were not monitored remotely.…”
Section: Discussionmentioning
confidence: 99%
“…A notable strength of all the home protocols was the possibility of measuring patients’ oxygen saturation at home and performing a QWT. More recently, several other studies reported the favorable experience of using telemedicine or remote monitoring in COVID-19 patients, all of which included the home measurement of oxygen saturation with a pulse oximeter [ 20 - 22 ]. For example, in a study by Gootenberg et al [ 20 ] approximately 10% of the patients that were initially discharged from the ED were admitted late to the hospital, as were 7% of them in the study by Tabacof et al [ 22 ] which is a slightly lower rate than in our cohort (17%).…”
Section: Discussionmentioning
confidence: 99%
“…Leveraging remote physiological monitoring (RPM) and telehealth care to address the longitudinal nature of chronic care across disease populations has significantly increased in recent years, particularly following the COVID-19 pandemic. [162][163][164] RPM is defined as the digital transmission of health data from a patient at home to their healthcare provider in a clinical location. 165,166 The use of RPM saw preliminary larger scale deployment in the management of patients with chronic cardiac and pulmonary conditions, with notable significance in reducing readmissions, reducing mortality rates, detecting clinical deterioration, and optimizing quality of life.…”
Section: Remote Monitoringmentioning
confidence: 99%